Zastosowanie pakietów statystycznych w szacowaniu ryzyka kredytów dla rolnictwa - Bryndza, Joanna (The Use of Statistical Packet in Credit Risk Assessment in Agriculture, 2005)
In the article there are described methods, which are practical in credit scoring in agriculture. In there article there are the stages of building of the model presented and changes that banks should introduce, especially in data accumulating.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 23-29